2014
DOI: 10.1016/j.neuroscience.2014.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Age-related increases in right frontal activation during task switching are mediated by reaction time and white matter microstructure

Abstract: Age-related increases in right frontal cortex activation are a common finding in the neuroimaging literature. However, neurocognitive factors contributing to right frontal over-recruitment remain poorly understood. Here we investigated the influence of age-related reaction time (RT) slowing and white matter (WM) microstructure reductions as potential explanatory factors for age-related increases in right frontal activation during task switching. Groups of younger (N = 32) and older (N = 33) participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…The location of the relationship between endothelial function and WM microstructure may be particularly important to the study of aging given that these tracts are especially vulnerable to age-related declines (Sullivan and Pfefferbaum, 2006 ; Bennett et al, 2010 ). The corpus callosum is one of the brain’s main commissural tracts that permits interhemispheric transmission of sensory, motor and cognitive information, and we have previously shown that WM microstructure in the genu of the corpus callosum mediates the relationship between age and the blood oxygen level dependent (BOLD) signal during task switching (Zhu et al, 2014 ). Collectively, these findings suggest that endothelial function is related to WM tracts important for maintaining neural efficiency and executive function.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the relationship between endothelial function and WM microstructure may be particularly important to the study of aging given that these tracts are especially vulnerable to age-related declines (Sullivan and Pfefferbaum, 2006 ; Bennett et al, 2010 ). The corpus callosum is one of the brain’s main commissural tracts that permits interhemispheric transmission of sensory, motor and cognitive information, and we have previously shown that WM microstructure in the genu of the corpus callosum mediates the relationship between age and the blood oxygen level dependent (BOLD) signal during task switching (Zhu et al, 2014 ). Collectively, these findings suggest that endothelial function is related to WM tracts important for maintaining neural efficiency and executive function.…”
Section: Discussionmentioning
confidence: 99%
“…The SFG is part of the dorsal lateral prefrontal cortex (DLPFC), a functional region implicated in age-related cognitive changes (Harlé Katia and Sanfey, 2012; Langner et al, 2015; MacPherson et al, 2002; Zhu et al, 2014). Compared to young adults, older adults show impaired performance in resolving stimulus–response conflict and decreased connectivity of bilateral AI to dorsomedial PFC and DLPFC (Langner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to young adults, older adults show impaired performance in resolving stimulus–response conflict and decreased connectivity of bilateral AI to dorsomedial PFC and DLPFC (Langner et al, 2015). Older adults, compared to younger adults, showed higher activation in the right DLPFC and right AI within a task-switching paradigm (Zhu et al, 2014). Within unfair offer trials of an economic decision task, older adults exhibited higher activation in the DLPFC and lower activation in bilateral AI relative to younger adults (Harlé Katia.…”
Section: Discussionmentioning
confidence: 99%
“…As a side note, we recall that a negative correlation indicates that better performance (lower switching and mixing costs) was associated with higher FA values. Age was not included as a covariate in correlation analysis, as all participants were selected to belong to a narrow age range, usually considered homogeneous in similar studies (e.g., Zhu et al, 2014 ). Threshold-Free Cluster Enhancement (TFCE) correction ( Smith and Nichols, 2009 ) was used to correct voxel-wise statistical results for multiple comparisons; significance level was set to be α = 5%, two-tailed.…”
Section: Methodsmentioning
confidence: 99%